Weight Minimization of In-plane Structure Using Implicit Floating Projection Topology Optimization - รัตนอุดม เสฏฐวุฒิ; Su, Rut; Tangaramvong, Sawekchai (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
This research introduces an innovative approach to minimizing the weight of in-plane structures using the implicit three-field Floating Projection Topology Optimization (FPTO) method. The FPTO method employs numerical simulation to enforce 0/1 design variable constraints, enabling the generation of clearly optimized designs with fewer intermediate elements. A key feature of this study is the adaptation of the original compliance minimization algorithm within the FPTO method, focusing on weight reduction driven by the maximum compliance ratio. Benchmark case studies validate the effectiveness of the proposed method, demonstrating weight reductions compared to existing techniques. Specifically, the method achieves a 10% weight saving in a two-bar truss. This result highlights the potential of using the FPTO method as an optimization tool for designing lightweight in-plane structures while maintaining structural performance.